Horizontal Gene Transfer Contributes to Plant Evolution: The Case of Agrobacterium T-DNAs - Quispe-Huamanquispe, Dora G.; Gheysen, Godelieve; Kreuze, Jan F. (Frontiers in Plant Science, 2017)
Horizontal gene transfer (HGT) can be defined as the acquisition of genetic material from another organism without being its offspring. HGT is common in the microbial world including archaea and bacteria, where HGT mechanisms are widely understood and recognized as an important force in evolution. In eukaryotes, HGT now appears to occur more frequently than originally thought. Many studies are currently detecting novel HGT events among distinct lineages using next-generation sequencing. Most examples to date include gene transfers from bacterial donors to recipient organisms including fungi, plants and animals. In plants, one well-studied example of HGT is the transfer of the tumor-inducing genes (T-DNAs) from some Agrobacterium species into their host plant genomes. Evidence of T-DNAs from Agrobacterium spp. into plant genomes, and their subsequent maintenance in the germline, has been reported in Nicotiana, Linaria and, more recently, in Ipomoea species. The transferred genes do not produce the usual disease phenotype, and appear to have a role in evolution of these plants. In this paper, we review previous reported cases of HGT from Agrobacterium, including the transfer of T-DNA regions from Agrobacterium spp. to the sweetpotato [Ipomoea batatas (L.) Lam] genome which is, to date, the sole documented example of a naturally-occurring incidence of HGT from Agrobacterium to a domesticated crop plant. We also discuss the possible evolutionary impact of T-DNA acquisition on plants.